An updated meta-analysis of the association between fibroblast growth factor receptor 4 polymorphisms and susceptibility to cancer. Issue 10 (23rd October 2020) - Moazeni-Roodi, Abdolkarim; Sarabandi, Sahel; Karami, Shima; Hashemi, Mohammad; Ghavami, Saeid
Abstract: Fibroblast growth factor receptor 4 (FGFR4) is a cell surface receptor tyrosine kinases (RTKs) for FGFs. Several studies have focused on the association between FGFR4 polymorphisms and cancer development. This meta-analysis aimed to estimate the association between FGFR4 rs351855 (Gly 388 Arg), rs1966265 (Val 10 Ile), rs7708357, rs2011077, and rs376618 polymorphisms and cancer risk. Eligible studies were identified from electronic databases. All statistical analyses were achieved with the STATA 14.0 software. Pooled odds ratios (ORs) with 95% confidence intervals (CIs) were used to quantitatively estimate the association. Overall, no significant association was found among rs351855, rs2011077, and rs376618 polymorphisms with the risk of overall cancer. The rs1966265 polymorphism significantly decreased the risk of cancer in recessive (OR = 0.87, 95% CI = 0.78–0.97, P =0.009, TT vs CT+CC) genetic model. Whereas the rs7708357 polymorphism was positively associated with cancer risk in dominant (OR = 1.17, 95% CI = 1.02–1.36, P =0.028) genetic model. Stratified analysis revealed that rs351855 variant significantly increased the risk of prostate cancer in heterozygous (OR = 1.16, 95% CI = 1.02–1.32, P =0.025 AG vs GG), dominant (OR = 1.20, 95% CI = 1.06–1.35, P =0.004, AG+AA vs GG), and allele (OR = 1.22, 95% CI = 1.06–1.41, P =0.005, A vs G) genetic models. In summary, the findings of this meta-analysis indicate that rs1966265, rs7708357, and rs351855 polymorphisms are correlated to cancer development. Further well-designed studies are necessary to draw more precise conclusions.